2017
DOI: 10.1017/s0033291717000654
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of risky drinking and associated harms from adolescence to young adulthood: findings from the Australian Temperament Project

Abstract: Continued patterns of risky alcohol use and related harms are apparent for both males and females across the twenties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This finding is likely explained by increases in alcohol consumption between these two timepoints due to the legal age of purchase and drinking at a licensed venue being 18 years of age in Australia (Australian Government Department of Health, 2019). Expanding on existing frameworks of alcohol‐related harm (Rehm, 2001; Zinberg, 1986) and the patterns of harm reported by Betts et al (2018), we also found that adolescents had heterogeneous patterns of experiencing harms across those that only affect the individual verses those that have interpersonal effects. Most of the cohort were represented across five patterns of alcohol‐related harms transition.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This finding is likely explained by increases in alcohol consumption between these two timepoints due to the legal age of purchase and drinking at a licensed venue being 18 years of age in Australia (Australian Government Department of Health, 2019). Expanding on existing frameworks of alcohol‐related harm (Rehm, 2001; Zinberg, 1986) and the patterns of harm reported by Betts et al (2018), we also found that adolescents had heterogeneous patterns of experiencing harms across those that only affect the individual verses those that have interpersonal effects. Most of the cohort were represented across five patterns of alcohol‐related harms transition.…”
Section: Discussionsupporting
confidence: 72%
“…Results of the multivariable multinomial logistic regression model are presented in Table 3 (see Supplemental Information Appendix for bivariate models). Late escalation to physiological harm was chosen as the reference class as it most closely reflects the Australian population in age of alcohol initiation (Australian Institute of Health & Welfare, 2020) and experience of harms (Betts et al, 2018). Female sex was associated with increased risk of experiencing early escalation to physiological harms (RR: 2.15; 99.5% CI: 1.19, 3.90) but was not associated with other transition patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations